Case Study on the Implementation of Evidence-Based Nursing: The Effect of Warm Lemongrass Decoction Compress on Pain Intensity in Gout Arthritis Patients - Novia, Resi; Lestari, Dian Trisna (Papua Medicine and Health Science, 2024)
Gout arthritis is a disease that causes pain in affected individuals. One non-pharmacological approach to reducing pain intensity in gout arthritis patients is warm compress therapy. Warm compresses can be combined with herbal plants to enhance their benefits, one of which is lemongrass (Cymbopogon citratus) through decoction. This case study aims to implement evidence-based warm lemongrass decoction compress therapy to reduce pain intensity in gout arthritis patients. This study employed a case study method, with a physical examination conducted using a head-to-toe assessment. Nursing diagnoses were determined based on the Indonesian Nursing Diagnosis Standard established by PPNI. The primary intervention was pain management using a non-pharmacological technique, specifically a warm lemongrass decoction compress. After six days of implementation, the pain was alleviated, with pain intensity decreasing from moderate to mild. The warm lemongrass decoction compress proved effective in reducing pain intensity in gout arthritis patients.